A comparative evaluation of spectrophotometric intracutaneous analysis and laser doppler imaging in the assessment of adult and paediatric burn injuries. Issue 7 (July 2018) - Charuvila, Somy; Singh, Masha; Collins, Declan; Jones, Isabel
Summary: Introduction: Clinical assessment of mid-dermal burns can be challenging. Currently, laser Doppler imaging (LDI) is the gold standard adjunct in the assessment of burn injuries. Although LDI has demonstrated reliable accuracy, it poses various limitations in routine use including cost and ease of use. In comparison, spectrophotometric intracutaneous analysis (SIA) is a relatively cheaper technique, which can be carried out using a modified digital camera that enables easy image acquisition. We aim to compare the accuracy of the two modalities in the assessment of mid-dermal burn injuries. Methods: We recruited 29 patients with mid-dermal burns presenting within 2 to 5 days post burn. Forty-five burn regions of interest were identified, and the patients underwent imaging using both the modalities. Subsequent clinical outcome was followed up and showed that treatment remained unaffected by participation. Two clinicians then independently predicted the healing potential of each burn region retrospectively as per images from either modality. Results: McNemar's test indicated that there is no significant difference between the accuracy of the two modalities (p = 0.61). Conclusion: The results suggest that the accuracy of SIA is comparable to that of LDI. Our experience with SIA indicates its potential as a cost-effective and user-friendly adjunct in decision-making.